How do you find the product of #(3a-b)(2a-b)#?

3 Answers

Answer:

Multiply each term in the parenthesis by each term in the other parenthesis, or better known as the FOIL method.

Explanation:

#(3a-b) (2a-b) #

#= (3a)(2a)+ (3a)(-b)+(-b)(2a)+(-b)(-b)#

#= 6a^2 + b^2 - 5ab#

May 2, 2018

Answer:

Formally, #(a + b) * (c + d) = ac + ad + bc + bd#.
When there are negative signs or subtraction involved, it may be helpful to re-write the equation in standard form.

Explanation:

#(3a - b)(2a - b) =#
#(3a + -b)(2a + -b)=#
#(3a * 2a) + (3a * -b) + (-b * 2a) + (-b * -b) =#
#6a^2 + (-3ab) + (-2ab) + (b^2)=#
#6a^2 -5ab + b^2#

May 2, 2018

Answer:

Please read below:

Explanation:

Consider making a table to list all the available terms in the binomials.

enter image source here

When you're multiplying binomials, you're multiplying each term of one binomial, with one of the other.

#3a times -b; 3a times 2a#
#-b times 2a; -b times -b#

This should get you #6a^2-5ab+b^2# as your product.